Regional 3D superimposition to assess temporomandibular joint condylar morphology - Schiing, J.; Gomes, L. C. R. [UNESP]; Benavides, E.; Nguyen, T.; Paniagua, B.; Styner, M.; Boen, V.; Gonçalves, João Roberto [UNESP]; Cevidanes, L. H. S. (British Inst Radiology, 2014)
Objectives: To investigate the reliability of regional three-dimensional registration and superimposition methods for assessment of temporomandibular joint condylar morphology across subjects and longitudinally.Methods: The sample consisted of cone beam CT scans of 36 patients. The across-subject comparisons included 12 controls, mean age 41.3 +/- 12.0 years, and 12 patients with temporomandibular joint osteoarthritis, mean age 41.3 +/- 14.7 years. The individual longitudinal assessments included 12 patients with temporomandibular joint osteoarthritis, mean age 37.8 +/- 16.7 years, followed up at pre-operative jaw surgery, immediately after and one-year post-operative. Surface models of all condyles were constructed from the cone beam CT scans. Two previously calibrated observers independently performed all registration methods. A landmark-based approach was used for the registration of across-subject condylar models, and temporomandibular joint osteoarthritis vs control group differences were computed with shape analysis. A voxel-based approach was used for registration of longitudinal scans calculated x, y, z degrees of freedom for translation and rotation. Two-way random intraclass correlation coefficients tested the interobserver reliability.Results: Statistically significant differences between the control group and the osteoarthritis group were consistently located on the lateral and medial poles for both observers. The interobserver differences were <= 0.2 mm. For individual longitudinal comparisons, the mean interobserver differences were <= 0.6 mm in translation errors and 1.2 degrees in rotation errors, with excellent reliability (intraclass correlation coefficient >0.75).Conclusions: Condylar registration for across-subjects and longitudinal assessments is reliable and can be used to quantify subtle bony differences in the three-dimensional condylar morphology.
Keywords: temporomandibular joint; reliability; measurements; registration; condyle; morphology